Uso de la inteligencia artificial en la educación universitaria: Exploración bibliométrica - Corzo-Zavaleta, Janet (2025)
This study aims to conduct a bibliometric analysis to investigate the current state of artificial intelligence (AI) adoption and utilization in higher education. A quantitative methodology was employed, analyzing 1476 scientific articles from renowned databases such as Scopus and Web of Science. Data was processed using the digital tools R and VOSviewer. The findings reveal an exponential growth in publications, with a growing focus on personalized learning, automated assessment, and the use of tools like ChatGPT. Significant international collaborations were identified; however, ethical challenges and the need for appropriate policies to ensure equitable and effective AI implementation in education were also highlighted. This study provides a global overview of research trends in AI in higher education, examining its applications, opportunities, and challenges for the teaching-learning process.